2013
DOI: 10.1111/zsc.12030
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of eriphioid crabs (Brachyura, Eriphioidea) inferred from molecular and morphological studies

Abstract: 2014). Phylogeny of eriphioid crabs (Brachyura, Eriphioidea) inferred from molecular and morphological studies.-Zoologica Scripta, 43, 52-64. The evolutionary relationships of the brachyuran crab superfamily Eriphioidea, commonly known as stone or rubble crabs, are examined. Analysis of three mitochondrial (12S, 16S and COI) and two nuclear loci (18S and Histone 3) was carried out for 51 taxa representing the Carpilioidea, Dairoidea, Eriphioidea, Goneplacoidea, Parthenopoidea, Pilumnoidea, Portunoidea, Pseudoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
4
15
0
Order By: Relevance
“…The result (Figure 1) showed that D. horrida is first clustered with Pseudocarcinus gigas and Myomenippe fornasinii, which revealed that Parthenopoidea is closer with Eriphioidea in Heterotremata. It is generally consistent with some previous studies (Lai et al 2014;Basso et al 2017;Tan et al 2018).…”
Section: Daldorfia Horrida; Mitochondrial Genome; Phylogenetic Analysissupporting
confidence: 93%
“…The result (Figure 1) showed that D. horrida is first clustered with Pseudocarcinus gigas and Myomenippe fornasinii, which revealed that Parthenopoidea is closer with Eriphioidea in Heterotremata. It is generally consistent with some previous studies (Lai et al 2014;Basso et al 2017;Tan et al 2018).…”
Section: Daldorfia Horrida; Mitochondrial Genome; Phylogenetic Analysissupporting
confidence: 93%
“…Although the composition of Xanthoidea has often been debated, several recent phylogenetic analyses support a monophyletic Xanthoidea sensu Ng et al . () (Thoma et al ., ; Lai et al ., , ; Lasley et al ., ). These reports, and other unpublished analyses, support the present selection of outgroup taxa including Eriphia gonagra (Fabricius, ), Lobopilumnus agassizii Stimpson, 1871 (Stimpson, 1871b), Menippe mercenaria (Say, ), and Acidops fimbriatus Stimpson, 1871 (Stimpson, 1871a), as these taxa have been shown to be related to but outside of Xanthoidea sensu Ng et al .…”
Section: Methodsmentioning
confidence: 99%
“…In order to reliably elucidate the evolutionary history of E. verrucosa , we specifically estimated the mutation rate of the Cox1 gene referring to the already surveyed phylogeny of the genus Eriphia by Lai et al [86], whose findings suggest congruence between geography and phylogeny in Eriphia . We, therefore, implemented a calibration point derived from the biogeographic event of the Pleistocene glacial sea-level low stands, assuming that the vicariant speciation of Indian and Indo-West Pacific species of the genus Eriphia might have been triggered by the impact of dry exposure of the Sunda Shelf at the onset of the Pleistocene glaciation cycles which occurred approximately 2.588 million years ago (± 0.005) [87, 88].…”
Section: Methodsmentioning
confidence: 99%
“…Before proceeding with the analysis, selection of the best-fit substitution model for the data was carried out with MODELTEST version 3.7 [90]. Cox1 sequences, corresponding to the eight examined species of the genus Eriphia by Lai et al [86] (GenBank accession numbers: HM638034-HM638038; KC771023-KC771024; KC962408) as well as to the haplotypes retrieved in our study, were used in the analysis. The two parameter Birth-Death model (considered as an appropriate null model for species diversification [91]), along with an uncorrelated lognormal relaxed clock, were used as priors for the analysis.…”
Section: Methodsmentioning
confidence: 99%